Towards a Smart Encapsulation System for Small-Sized Electronic Devices: A New Approach - Sebastian-Tim Schmitz-Hertzberg; Rick Liese; Carsten Terjung; Frank F. Bier (International Journal of Polymer Science)
Miniaturized analytical chip devices like biosensors nowadays provide assistance in highly diverse fields of application such as point-of-care diagnostics and industrial bioprocess engineering. However, upon contact with fluids, the sensor requires a protective shell for its electrical components that simultaneously offers controlled access for the target analytes to the measuring units. We therefore developed a capsule that comprises a permeable and a sealed compartment consisting of variable polymers such as biocompatible and biodegradable polylactic acid (PLA) for medical applications or more economical polyvinyl chloride (PVC) and polystyrene (PS) polymers for bioengineering applications. Production of the sealed capsule compartments was performed by heat pressing of polymer pellets placed in individually designable molds. Controlled permeability of the opposite compartments was achieved by inclusion of NaCl inside the polymer matrix during heat pressing, followed by its subsequent release in aqueous solution. Correlating diffusion rates through the so made permeable capsule compartments were quantified for preselected model analytes: glucose, peroxidase, and polystyrene beads of three different diameters (1.4 μm, 4.2 μm, and 20.0 μm). In summary, the presented capsule system turned out to provide sufficient shelter for small-sized electronic devices and gives insight into its potential permeability for defined substances of analytical interest.